AB0509 Identification of novel biomarkers associated with disease activity of primary sjÖgren's syndrome and clinical response to vay736. (15th June 2017) - Doucet, J; Kazma, R; Cabanski, M; Kamphausen, E; Maguire, P; Avrameas, A; Valentin, M-A; Li, Y; Auger-Sarrazin, A; Kaiser, S; Follet, P; Oliver, S; et al.
Abstract : Background: Overexpression of B cell activating factor (BAFF) contributes to the pathogenesis of primary Sjögren's syndrome (pSS) [1]. Treatment of pSS patients with VAY736, an anti-human BAFF receptor mAb, appears promising and was associated with a positive therapeutic effect [2]. Given the complexity and heterogeneity of pSS, there is a need to further identify molecular mechanisms involved in pSS and in response to new therapeutics. Objectives: To address this question, we assessed a panel of biomarkers in 27 patients from a clinical trial and tested their associations with pSS activity and clinical response to VAY736. Methods: This study comprised 27 pSS patients treated with a single intravenous dose of VAY736 at 10 mg/kg (n=12), 3 mg/kg (n=6), or placebo (n=9). The disease activity scores included EULAR Sjogren's Syndrome Disease Activity Index (ESSDAI) and Patient Reported Index (ESSPRI), patient's and physician's reported visual analog scales (VAS), Short-Form 36 and Multidimensional Fatigue Inventory (MFI). BAFF and a panel of chemokines in serum and saliva were assessed using immunoassays. Circulating B cells and B cell subsets were measured by flow cytometry. High frequency ultrasound (US) of the parotid and sub-mandibular glands measured gland thickness and quality using a 4 point scoring (de Vita) [3]. Shear wave elastography of the parotid glands was also measured. All biomarkers were measured at baseline (BL) and post-treatment w6, w12, w24. The effect of VAY736 on biomarker levels was assessed by descriptive statistics. Correlations between biomarkers and disease activity scores were calculated at BL and w6, w12, and w24 using levels and relative changes from BL. Results: In addition to B cell depletion, serum BAFF increase, and improvements in US and elastography measures [2], a subset of serum chemokine tended to be reduced nine weeks after VAY736 treatment. Pooling all 27 patients, salivary BAFF levels correlated with parotid De Vita scores at BL (left: r=0.75, right: r=0.72, p<10 -4 for both) and w6 (left: r=0.72, ; right: r=0.78, p<10 -4 for both) but not at later time points. Pooling the 18 VAY736 treated patients, increase in salivary BAFF correlated with decrease in MFI at w6 (r=-0.83, p=3×10 -4 ) and high levels of one of the serum chemokines at BL correlated with decrease in ESSPRI at w24 (r=-0.76, p=3×10 -4 ). In the same patients, the B cell count at BL correlated with changes in several clinical outcomes at w12: ESSPRI (r=-0.65, p=0.01), Physician's VAS (r=-0.6, p=0.01), shear wave (r=-0.63, p=0.02), and parotid thickness (r=-0.6, p=0.03). Conclusions: We identified a set of markers correlated with clinical outcomes in pSS after treatment with VAY736, which have the potential to provide additional insight in pSS and treatment-modifying effects. Further large-scale studies are necessary to confirm the value of these markers. References: Varin MM et al. Autoimmun Rev 2010;9(9):604–8. Dörner T et al. Arthritis Rheum 2016; 68(suppl S10):4051. De Vita S, et al. Clin Exp Rheumatol 1992;10:351–6. Disclosure of Interest: J. Doucet Employee of: Novartis AG, R. Kazma Employee of: Novartis AG, M. Cabanski Employee of: Novartis AG, E. Kamphausen Employee of: Novartis AG, P. Maguire Employee of: Novartis AG, A. Avrameas Employee of: Novartis AG, M.-A. Valentin: None declared, Y. Li Employee of: Novartis AG, A. Auger-Sarrazin Employee of: Novartis AG, S. Kaiser Employee of: Novartis AG, P. Follet Employee of: Novartis AG, S. Oliver Employee of: Novartis AG, A. Vitaliti Employee of: Novartis AG